Neuropsychiatric dimensions of COVID-19 - literature review - Iga Kozińska; Rafał Oleszczuk; Anna Kozińska; Anna Oleszczuk (Kazimierz Wielki University, 2022)
SARS-CoV-2 infection leads to severe multiple organ failure. The immune system is stimulated by activating the inflammatory mechanism and by releasing inflammatory cytokines. COVID-19 is able to penetrate the central nervous system, inducing neuritis and neurodegeneration. In our study, we analyzed the latest available articles. We focused on the subject of COVID-19 infection and consequences of neuroinflammation. For this study, we searched the literature available in Pubmed and Google Scholar databases using keywords. There is evidence of a common background of COVID-19 complications and neurological diseases such as Parkinson's or Alzheimer's disease. This type of complication is more frequently observed in serious cases of COVID-19, with a more intense immune response, with higher levels of CRP, ferritin and D-dimers. Organic changes in conjunction with environmental stress caused by the experience of severe illness, fear of becoming ill and social limitations, lead to neuropsychiatric pathologies, including major depressive disorders and post-traumatic stress. The neuropsychiatric implications of COVID-19 represent a severe clinical problem that deserves special attention in the treatment of COVID-19 infection. There is a need to monitor the neuropsychiatric consequences of COVID-19, in order to completely understand the impact of SARS-CoV-2 infection. This knowledge is necessary to be able to confront the public health crisis created by the COVID-19 pandemic.